2020
DOI: 10.1177/2325967120905526
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Work After Articular Cartilage Repair Intervention: A Systematic Review

Abstract: Background: The process of returning to work after cartilage treatment has not been studied in depth, even though a better understanding of potential outcomes could lead to significant benefits for the general population. Purpose: To determine which surgical interventions are most effective in helping patients return to work after cartilage repair and to identify factors that affect the ability to return to work. Study Design: Systematic review; Level of evidence, 4. Methods: This systematic review followed PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A recent systematic review depicted almost 100% return to work rates after ACI plus HTO whereas a significantly less number of patients (51.78%) returned to their former work activity after osteochondral allograft transplantation. 22 HTO in combination with ACI also led to the shortest return to work time (3.15 months) compared to ACI alone (3.34 months) and osteochondral allograft (11.1 months). Multiple studies and even systematic reviews and meta-analyses on the effect of high tibial osteotomy with a concomitant "cartilage procedure" in osteoarthritic knees compared with HTO alone exist, 11,[23][24][25][26][27] but literature about cartilage procedures with versus without concomitant high tibial osteotomy in patients with focal cartilage defects is sparse.…”
Section: Discussionmentioning
confidence: 90%
“…A recent systematic review depicted almost 100% return to work rates after ACI plus HTO whereas a significantly less number of patients (51.78%) returned to their former work activity after osteochondral allograft transplantation. 22 HTO in combination with ACI also led to the shortest return to work time (3.15 months) compared to ACI alone (3.34 months) and osteochondral allograft (11.1 months). Multiple studies and even systematic reviews and meta-analyses on the effect of high tibial osteotomy with a concomitant "cartilage procedure" in osteoarthritic knees compared with HTO alone exist, 11,[23][24][25][26][27] but literature about cartilage procedures with versus without concomitant high tibial osteotomy in patients with focal cartilage defects is sparse.…”
Section: Discussionmentioning
confidence: 90%
“…There are few studies of the timing of return to ADL and/or work following ACI/MACI published in the literature, and there is limited information for the type and demand of the work. 28 Therefore, obtaining consensus on these milestones was important so that realistic expectations for patients and surgeon guidance can be established for MACI. One case series study by Pestka et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the German Cartilage Registry, Faber et al 83 reported that concomitant osteotomy results in better postoperative KOOS values, lower pain levels, and a higher patient satisfaction when combined with cartilage repair. The systematic review of 2020 by Nimkingratana et al 90 concluded that when osteotomy was associated with cartilage procedures, increased rates of repairs and shorter periods to return to work were seen. For focal cartilage defects, osteotomy could therefore act as a solid foundation for the reconstruction of the lesion.…”
Section: Potential Of Osteotomy Alone To Suffice For Focal Cartilage ...mentioning
confidence: 99%